An Update on Protective Effectiveness of Immune Responses After Recovery From COVID-19 - Soleimanian, Saeede; Alyasin, Soheila; Sepahi, Najmeh; Ghahramani, Zahra; Kanannejad, Zahra; Yaghobi, Ramin; Karimi, Mohammad Hossein (Frontiers in Immunology, 2022)
Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) exhibits variable immunity responses among hosts based on symptom severity. Whether immunity in recovered individuals is effective for avoiding reinfection is poorly understood. Determination of immune memory status against SARS-CoV-2 helps identify reinfection risk and vaccine efficacy. Hence, after recovery from COVID-19, evaluation of protective effectiveness and durable immunity of prior disease could be significant. Recent reports described the dynamics of SARS-CoV-2 -specific humoral and cellular responses for more than six months in convalescent SARS-CoV-2 individuals. Given the current evidence, NK cell subpopulations, especially the memory-like NK cell subset, indicate a significant role in determining COVID-19 severity. Still, the information on the long-term NK cell immunity conferred by SARS-CoV-2 infection is scant. The evidence from vaccine clinical trials and observational studies indicates that hybrid natural/vaccine immunity to SARS-CoV-2 seems to be notably potent protection. We suggested the combination of plasma therapy from recovered donors and vaccination could be effective. This focused review aims to update the current information regarding immune correlates of COVID-19 recovery to understand better the probability of reinfection in COVID-19 infected cases that may serve as guides for ongoing vaccine strategy improvement.